PESERTA DIDIK DAN PENDIDIK PERSPEKTIF HADITS - Muhammad Polem; Maslani Maslani; Reksahati Wulandari (JURNAL EDUCATION AND DEVELOPMENT, 2024)
This study aims to provide an overview of the nature of students and educators from the Hadith perspective. The writing method in this article uses literature study with a qualitative approach. The results of this study reveal several hadiths that talk about students, as contained in H.R Bukhari, No.69, H.R Ibnu Majah, No.220, H.R Bukhari, No.116, and H.R Abu Daud, No.4091. While the hadiths that discuss educators are contained in H.R At-Tirmidhi, No. 2609, and H.R Bukhari, No. 95. Of course the hadiths mentioned above are a small part of the hadiths that discuss students and educators. The conclusion in this study is that in essence every human being can be called a learner and can also be called an educator, depending on the situation and conditions. Efforts made by educators and students in the educational process aim to create students who are intellectually intelligent and have noble manners, morals, and morals as a whole.